Preferential trade agreements : a law and economics analysis / Kyle W. Bagwell, Petros C. Mavroidis. - Bagwell, Kyle; Mavroidis, Petros C. (Cambridge University Press, 2011)
This volume assembles a stellar group of scholars and experts to examine preferential trade agreements (PTAs), a topic that has time and again attracted the interest of analysts. It presents a discussion of the evolving economic analysis regarding PTAs and the various dysfunctions that continually place them among the priority items for (re)negotiation by the WTO. The book explores recent empirical research that casts doubt on the old 'trade diversion' school and debates why the WTO should deal with PTAs and if PTAs belong under the mandate of the WTO as we now know it.